Two Important Issues in Environmental Ethics: Cloning and Genetic Engineering - Tsekos, Christos A.; Bissa, Marianna N. (Scientific Research, 2017)
This paper aims to investigate the moral dilemmas that arise in two contemporary issues, those of Cloning and Genetic Engineering. Firstly, we examine some purely technical aspects of these two issues. Secondly, we attempt an analysis of the moral and social dimensions of Cloning and Genetic Engineering. We argue that total rejection of Cloning and Genetic Engineering is neither sound nor documented, and we conclude that there are significant benefits from these two technologies. Additionally, we propose a set of actions that will help modern societies to cope effectively with these challenges.
Keywords: Cloning; Genetic Engineering; Environmental Ethics; Values; Technology